Scientific English a guide for scientists and other professionals - Day, Robert A. 1924- (Greenwood, 2011)
English language has a vocabulary of upwards of 500,000 words, it only uses nine parts of speech, and all of these words falls into one (or more) of those nine categories. This title contains many simple revelations like this that make effective scientific writing in English easy, even for those whose fluency in another language.